2018
DOI: 10.1159/000496698
|View full text |Cite
|
Sign up to set email alerts
|

Brain Morphology in Patients with Genetic Generalized Epilepsy: Its Heterogeneity among Subsyndromes

Abstract: Background: We aimed to evaluate the brain morphology of patients with genetic generalized epilepsy (GGE) compared to healthy subjects. In addition, we investigated whether there are differences in brain morphology among different GGE syndromes. Methods: We enrolled 100 patients with a clinical diagnosis of GGE. The patients were classified into different syndrome groups according to their predominant seizure type, age of seizure onset, and electroencephalography characteristics (12 childhood absence epilepsy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 24 publications
2
5
0
Order By: Relevance
“…Simultaneous acquisition of EEG-fMRI showed significantly reduced connectivity between DMN and the occipital cortex in patients with IGE and uncontrolled seizures [20]. Studies have also reported aberrant cortical thickness and gray matter volume in the occipital lobe in patients with JME, mainly in the fusiform, lingual gyrus, and lateral occipital cortex [21,22]. Our results of decreased functional activity and global connectivity in the occipital cortex are consistent with those findings.…”
Section: Discussionsupporting
confidence: 90%
“…Simultaneous acquisition of EEG-fMRI showed significantly reduced connectivity between DMN and the occipital cortex in patients with IGE and uncontrolled seizures [20]. Studies have also reported aberrant cortical thickness and gray matter volume in the occipital lobe in patients with JME, mainly in the fusiform, lingual gyrus, and lateral occipital cortex [21,22]. Our results of decreased functional activity and global connectivity in the occipital cortex are consistent with those findings.…”
Section: Discussionsupporting
confidence: 90%
“…Existing studies show that 30% of JME patients are photosensitive (Wolf and Goosses, 1986). Some studies have found that there are abnormal cortical thickness and gray matter volume in the occipital lobe of JME patients, and most of them occur in the fusiform, lingual gyrus, and lateral occipital cortex (Park et al, 2018). Our results support the abnormal structure and functional performance of the above nodes.…”
Section: Discussionsupporting
confidence: 85%
“…Another frequent CT pathology was cerebral atrophy, which is a common finding in PWE, but the significance and aetiology is hard to determine [26]. The rate of this pathology was higher in patients with general onset seizures, which is also known from previous studies, where patients with idiopathic generalised and genetic seizure syndromes showed diffuse and wide-spread alterations of brain morphology [26][27][28]. Detailed MRI analyses in these patients sometimes also reveal (wide-spread) cerebral malformations such as lissencephaly with pachygyria or microgyria potentially causing both focal and generalized seizures [29].…”
Section: Discussionmentioning
confidence: 84%